EXPERIENCE OF TREATMENT WITH ABATACEPT IN CHILD WITH JUVENILE RHEUMATOID ARTHRITIS AND SECONDARY INEFFICIENCY OF INFLIXIMAB - I.P. Nikishina; V.A. Malievskiy; E.S. Fedorov; E.P. Pervushina; A.Zh. Nuriakhmetova ("Paediatrician" Publishers LLC, 2011)
Opportunities of effective treatment of juvenile arthritis became wide because of introduction of genetically engineered biological drugs to the clinical practice during last years. One of the genetically engineered drugs of first choice for the treatment of refractory types of juvenile arthritis is tumor necrotizing factor blocker infliximab. Nowadays the problem of its primary and secondary inefficiency becomes topical. The article presents an experience of treatment with abatacept in patient with polyarticular type of juvenile rheumatoid arthritis with eyes lesion. Successful treatment with abatacept in patient with high active polyarthritis and uveitis resistant to infliximab proves reasonability of therapy of different clinical symptoms of juvenile arthritis with abatacept.Key words: children, juvenile rheumatoid arthritis, infliximab, abatacept, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 170-174)